Breaking the Borders of Fantasy: Travelling through the Stillness in N. K. Jemisin’s Broken Earth Trilogy - Mateus, Rui (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2021)
As the genre of fantasy literature continues to grow, new authors strive to innovate and stray from the traditional principles that ruled it for many decades when epic fantasy was more prominent. Though epic features still remain a great part of the genre, the characteristics that rule fantasy worlds, stories, and characters have changed over time, bringing new aspects into the fold and introducing new voices. As academics attempt to categorize a genre as diverse as fantasy to better understand it and define it, authors continue to expand and mingle fantasy elements with components from other genres, especially science-fiction. The aim of this article is to identify how a taxonomy of fantasy can be used to understand the relation between the fantastic and the narrative. By analyzing N. K. Jemisin’s novels in the Broken Earth trilogy through Farah Mendlesohn’s categorization of fantasy proposed in Rhetorics of Fantasy (2008), the goal is to discover the aspects in which Jemisin brings innovation into the fantasy genre by applying elements from various categories.